2016
DOI: 10.1007/s11626-016-0078-1
|View full text |Cite
|
Sign up to set email alerts
|

Fat body and hemocyte contribution to the antimicrobial peptide synthesis in Calliphora vicina R.-D. (Diptera: Calliphoridae) larvae

Abstract: Antimicrobial peptides accumulated in the hemolymph in response to infection are a key element of insect innate immunity. The involvement of the fat body and hemocytes in the antimicrobial peptide synthesis is widely acknowledged, although release of the peptides present in the hemolymph from the immune cells was not directly verified so far. Here, we studied the presence of antimicrobial peptides in the culture medium of fat body cells and hemocytes isolated from the blue blowfly Calliphora vicina using compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 24 publications
0
22
0
2
Order By: Relevance
“…Surprisingly, we observed that circulating hemocytes containing AMPs were associated with the LG tumors. However, previous studies have reported that Drosophila AMPs stored in the cytoplasmic granules of circulating hemocytes were discharged against infecting microbes (Destoumieux et al, 2000; Yakovlev et al, 2017). Moreover, AMP-containing hemocytes are reportedly recruited to neoplastic tumors in Drosophila (Cordero et al, 2010; Parisi et al, 2014; Pastor-Pareja et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, we observed that circulating hemocytes containing AMPs were associated with the LG tumors. However, previous studies have reported that Drosophila AMPs stored in the cytoplasmic granules of circulating hemocytes were discharged against infecting microbes (Destoumieux et al, 2000; Yakovlev et al, 2017). Moreover, AMP-containing hemocytes are reportedly recruited to neoplastic tumors in Drosophila (Cordero et al, 2010; Parisi et al, 2014; Pastor-Pareja et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, AMP-containing hemocytes are reportedly recruited to neoplastic tumors in Drosophila (Cordero et al, 2010; Parisi et al, 2014; Pastor-Pareja et al, 2008). Subsequently, the hemocytes release the stored AMPs against the tumor cells by regulated exocytosis (Destoumieux et al, 2000; Yakovlev et al, 2017). In this study, we showed that Drosomycin and Defensin have an anti-tumor activity against hematopoietic tumors with the help of circulating hemocytes in the hemolymph.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the haemocytes were recruited into the LG tumours. Previous studies have reported that Drosophila AMPs stored in the cytoplasmic granules of circulating haemocytes were discharged against infectious microbes (Destoumieux et al, 2000; Yakovlev et al, 2017). Moreover, AMP-containing haemocytes are reportedly recruited to neoplastic tumours in Drosophila (Cordero et al, 2010; Parisi et al, 2014; Pastor-Pareja et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…They have been shown to be mainly effective against Gram-positive bacteria, such as MRSA and its strains ( Andersen et al, 2010 ; Cerovsky and Bem, 2014 ). Amongst the most recent studies on antimicrobial peptides isolated from flies from the Calliphoridae family different to those obtained from larval ES, it is worth mentioning a study by Yakovlev et al (2017) ( Yakovlev et al, 2017 ), who studied the presence of AMPs in the culture medium from both fat bodies and haemocytes derived of Calliphora vicina larvae. They demonstrated that both cell types synthesized and released an AMPs complex to the culture medium, corresponding to defensins, cecropins, diptericins, and proline-rich peptides.…”
Section: Introductionmentioning
confidence: 99%